힐링(Healing)과 연관된 개념의 변천과 트렌드 동향 분석 - 웰빙(Well-being), 웰니스(Wellness), 힐링(Healing)의 키워드를 중심으로 - 최지안; Choe Ji An; 이진민; Rhie Jin Min (기초조형학연구, 2019)
21세기 사회는 편리한 생활과 물질적 풍요로움 속에 있지만 오염된 환경과 다양한 질병 등 심한 스트레스로 인한 몸과 마음의 치유와 회복을 추구하는 이상적인 힐링을 지향하게 되면서, 다양한 힐링 문화가 모든 영역으로 전파되며 변화하고 있다. 이러한 변화와 동향을 파악하기 위한 연구 방법으로 힐링과 연관된 개념의 문헌과 자료 수집, 선행연구를 바탕으로 학술논문의 분야별 특성을 재정리하여 분류분석의 기반을 마련하였다. 연구의 분석범위는 1996년부터 2018년까지 국내의 KCI등재된 국내 학술논문으로 한정하여 ‘웰빙’, 웰니스’, ‘힐링’을 키워드로 내용분석법을 이용하였다. 따라서 본 연구는 힐링과 연관된 개념(웰빙, 웰니스, 힐링)의 시대적 변천과정에 따라 나타나는 힐링과 연관된 개념의 내용과 추세의 흐름에 관한 성향을 파악하여, 힐링 트렌드의 동향을 파악하고 특성을 밝히는 것에 목적이 있다. 그 결과 ‘웰빙’은 532편, ‘웰니스’는 573편, ‘힐링’은 229편으로 조사되었다. 분야별 분석 결과 ‘웰빙’은 인문·사회 >예술·체육 >자연·과학>공학·기타 순으로 조사되었고, ‘웰니스’에서는 예술·체육>인문·사회>자연·과학>공학·기타의 순으로 조사되었다. ‘힐링’은 인문·사회>예술·체육 >자연·과학>공학·기타의 순으로 조사되었다. 다양한 분야에서 힐링과 연관된 개념들의 연구 경향이 나타났고, 2013년 이후로는 ‘웰니스’의 연구가 월등히 높아지고 있었다. 이는 다양한 영역의 광범위한 분야의 결합과 확대로 이어지고, 환경문제의 심각성과 기상변화가 일상화 되는 현대에서는 친환경이 아니라 이제는 필(必)환경시대에 진입했다는 사회적 분위기로 웰니스의 모든 요소가 필수적인 힐링을 위한 기본 요소가 되고 있으며, 힐링 공간은 총체적 복합 문화공간으로 변화되는 것을 알 수 있다. 끝으로 본 연구는 힐링과 연관된 개념(웰빙, 웰니스, 힐링)의 변천과 힐링 트렌드 동향을 조명하고, 힐링과 연관된 연구에 유용한 자료로 활용되기를 기대한다. Although the 21st century society is in a convenient life and material abundance, it is aimed at the ideal healing that pursues the healing and recovery of the body and mind caused by the severe stress such as polluted environment and various diseases, It is spreading and changing. Based on the literature, data collection, and previous research on the concepts related to healing, research methods to grasp these changes and trends were reorganized and the basis of classification analysis was laid out. This study aims to comprehend content and trend flow of Healing-related concepts such as Well-being, Wellness and Healing over the changes of the times and consequently reveal features of Healing trends. The subjects of analysis were selected within the treatises of domestic academic journal, KCI, registered from 1996 to 2018 by applying a content analysis method with keywords: ‘Wellbeing’, ‘Wellness’ and ‘Healing’. The search result showed 532 papers found with a key word ‘Wellbeing’, 573 for ‘Wellness’ and 229 for ‘Healing’. According to the results of sectorial analysis, Wellbeing was surveyed in the order of Humanities and Social Science > Arts and Physical Education > Nature and Science > and Engineering and others. Wellness was in the ordered of Arts and Physical Education > Humanities and Social Science > Nature and Science > Engineering and others. Lastly, Healing was in the order of Humanities and Social Science > Arts and Physical Education > Nature and Science > Engineering and others. The Research trends of Healing-related concepts were observed in various disciplines, and the studies in a field of Arts and Physical Education which include Design, Interior, Beauty Art, Physical Education, Health Care and Life Health Management, was especially shown to have increased both quantitatively and qualitatively. The number of studies on Wellness started to outstandingly increase since 2013. This leads to a combination of diverse fields, and in modern times where environmental problems and weather changes are common, all elements of Wellness are becoming essential elements for healing. It can be seen that Healing space inseparably applied to life is transformed into a total complex cultural space pursuing essential happiness of human beings. In conclusion, this study aims to illuminate the transitions of Healing-related concepts and Healing trends, and is sincerely hoped to be a useful resource for future studies related to Healing.